2001
DOI: 10.1046/j.1528-1157.2001.10900.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vagus Nerve Stimulation on Epileptiform Activity Recorded from Hippocampal Depth Electrodes

Abstract: Summary: Purpose:To assess the effect of vagus nerve stimulation (VNS) on interictal epileptiform activity in the human hippocampus. Clinical studies have established the efficacy of vagus nerve stimulation in patients with epilepsy (VNS Study Group, 1995), although the electrophysiologic effects of VNS on the human hippocampus and mesial temporal lobe structures remain unknown.Methods: We report a case study in which a patient with an implanted VNS underwent intracranial electrode recording before temporal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 16 publications
(25 reference statements)
1
30
0
5
Order By: Relevance
“…The performance of standard EEG, recorded for only 40 min in the present study,was not optimally suited to detect significant variations in spiking activity. However, previous studies with longer periods of EEG monitoring have shown that long-term VNS induces a delay in interspiking activity and a reduction in the frequency of epileptic interictal spikes (Koo, 2001;Kuba et al, 2002;Olejniczak et al, 2001), though a recent study which evaluated in children whether spike rates are useful as an outcome parameter following VNS yielded contrasting results (Ebus et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The performance of standard EEG, recorded for only 40 min in the present study,was not optimally suited to detect significant variations in spiking activity. However, previous studies with longer periods of EEG monitoring have shown that long-term VNS induces a delay in interspiking activity and a reduction in the frequency of epileptic interictal spikes (Koo, 2001;Kuba et al, 2002;Olejniczak et al, 2001), though a recent study which evaluated in children whether spike rates are useful as an outcome parameter following VNS yielded contrasting results (Ebus et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years VNS has been shown in several animal studies, and recently in some human studies to suppress both ictal and interictal epileptiform EEG activity. [10][11][12][13][14] In an earlier report we present the findings that VNS reduces interictal epileptiform discharges in Rapid eye movement (REM) and slow wave sleep (SWS), and the number of electrographic seizures. 15 The effects of VNS on sleep in patients with medically refractory epilepsy have only been elucidated in a few studies and so far not in children.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios refieren cambios en la frecuencia de base en el EEG, dependiendo de la intensidad de la estimulación. Utilizando electrodos intracraneales se han encontrado cambios en la frecuencia de las descargas epileptiformes 55 . Otros estudios, sin embargo, no han confirmado cambios en el EEG, ni a simple vista ni en el análisis de frecuencias 23,45,66 .…”
Section: Figura 5 Instantánea Quirúrgica Del Electrodo Tunelizado Y unclassified